Online Travel Purchasing. A Literature Review - Amaro, Suzanne (2015)
Over the past two decades, there has been an increasing focus on the development of Information and Communication Technologies (ICTs), as well as the impact that they have had on the tourism industry and on travelers’ behaviors. However, research on what drives consumers to purchase travel online has typically been fragmented. In order to better understand consumers’ behavior toward online travel purchasing, this article offers a review of articles that were published in leading tourism and hospitality journals, the ENTER proceedings, and several articles from other peer-reviewed journals, found on the main academic search databases. The antecedents of online travel shopping found are classified into three main categories: Consumer Characteristics, Perceived Channel Characteristics, and Website and Product Characteristics. Finally, this study identifies several gaps and provides some orientation for future research.